Nutrition for Children Involved in Sports (Eurasian Research Bulletin, 2022)
In the development of sports nutrition, at all stages of the exercise process, the scientific substantiation of approaches to the diet of athletes remains relevant. The aim is to conduct evidence-based research to develop a methodological framework for nutrition based on individual characteristics of the organism, as well as to evaluate a set of measures for the organization of functional nutrition.